Can Basic Medical Insurance Reduce Elderly Family Income Inequality in China? - Pu, Xiaohong; Wang, Yilong; Zhang, Weike; Zeng, Ming (Frontiers in Public Health, 2022)
Basic medical insurance is the critical medical security system to realize common prosperity in China. This study explores the impact of basic medical insurance on elderly income inequality in China using the China Family Panel Studies (CFPS) data in 2018. Our finding shows that basic medical insurance is significantly negatively correlated with elderly income inequality, indicating basic medical insurance has a positive impact on narrowing the elderly income inequality. The heterogeneity analysis shows that basic medical insurance has a more significant improvement effect among the urban elderly and the younger elderly. We also find that health performance significantly mediates the relationship between basic medical insurance and elderly income inequality. The implication of this study is that the Chinese government should increase the proportion of basic medical insurance reimbursement and continue to expand the scope of reimbursement for basic medical insurance to realize income fairness among the elderly.